2005
DOI: 10.1063/1.1887170
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved imaging of the reaction coordinate

Abstract: Time-resolved photoelectron imaging of negative ions is employed to study the dynamics along the reaction coordinate in the photodissociation of IBr(-). The results are discussed in a side-by-side comparison with the dissociation of I(2) (-), examined under similar experimental conditions. The I(2) (-) anion, extensively studied in the past, is used as a reference system for interpreting the IBr(-) results. The data provide rigorous dynamical tests of the anion electronic potentials. The evolution of the energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 76 publications
2
45
0
Order By: Relevance
“…2(c), we conclude that the delayed rise of the experimental signal is not due to the energy difference between the B state of IBr − and the electronic state of IBr accessed by probe photodetachment. Interestingly, in the earlier study 33,48 of the TRPES obtained by first exciting IBr − to the A state followed by detachment, we found that both experiment and calculation displayed an instantaneous rise of the signal. The electronic character of the anion and neutral states evolves rapidly at short I-Br distances, i.e., in the "molecular" regime, yet we do not have the information needed to incorporate the internal coordinate dependence of the detachment cross-sections in the calculated spectra.…”
Section: B Photodissociation Of Ibr −mentioning
confidence: 69%
“…2(c), we conclude that the delayed rise of the experimental signal is not due to the energy difference between the B state of IBr − and the electronic state of IBr accessed by probe photodetachment. Interestingly, in the earlier study 33,48 of the TRPES obtained by first exciting IBr − to the A state followed by detachment, we found that both experiment and calculation displayed an instantaneous rise of the signal. The electronic character of the anion and neutral states evolves rapidly at short I-Br distances, i.e., in the "molecular" regime, yet we do not have the information needed to incorporate the internal coordinate dependence of the detachment cross-sections in the calculated spectra.…”
Section: B Photodissociation Of Ibr −mentioning
confidence: 69%
“…12 ͑Fig. The corresponding images were reported previously alongside the similar measurements on IBr − , 12 albeit without discussing the angular distributions.…”
Section: Electron-localization Time Scalementioning
confidence: 83%
“…6,12,13 In brief, it employs pulsed negative-ion generation and mass-analysis techniques, 14,15 combined with a velocity-mapped, 16 imaging 17,18 scheme for the detection of photoelectrons. 6,12,13 In brief, it employs pulsed negative-ion generation and mass-analysis techniques, 14,15 combined with a velocity-mapped, 16 imaging 17,18 scheme for the detection of photoelectrons.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…In this instance it can be seen that the full width at half maximum of the narrowest peak in the spectrum is around 50 meV, or 400 cm À1 and the resolution is limited by the detection method. Femtosecond time-resolved VMI has been successfully applied to the study of energy redistribution processes in neutral molecules [12,26,27], and in anions [28,29], and in some of these studies photoelectron angular distributions have also been analysed, see Section 5. However, we note that the photoelectron spectra obtained have insufficiently good resolution to enable the characterization of dark vibrational states that may have been populated by IVR; such resolution is generally precluded by the laser bandwidth.…”
Section: Velocity Map Imagingmentioning
confidence: 99%